Sistem Pendukung Keputusan Seleksi Karyawan Admisi dan Pemasaran di Universitas Trilogi menggunakan AHP - Silvester Dian Handy Permana (STMIK Budi Darma, 2024)
In the era of global competition in the world of higher education, effective and efficient employee selection is the main key to achieving university strategic goals. This research uses the Process Hierarchy Analysis (AHP) method as a basis for making employee selection decisions at the Admissions and Marketing Bureau at Trilogi University. The AHP method has proven effective in overcoming complexity and subjectivity in the employee selection process by considering various important factors that influence decisions. This research focuses on the implementation of an AHP-based decision support system (DSS) which was developed specifically for employee selection needs in bureaus that play a role in designing and managing student admission strategies and university promotions. Factors considered in calculating AHP include age, work experience, specific work experience in the marketing field, administrative skills, English language skills, and attitude when conducting interviews. This system provides a holistic view in candidate assessment by prioritizing these factors according to the weight given by decision makers. The results of this research are recommendations in a ranking system for the best candidates to become employees at Trilogy University. Employees accepted in this selection process are A2 and A1 based on the University's needs. This research combines best practices in human resource management with a technology-based approach to produce innovative solutions in employee selection decision making.